The Jurisprudential Exegetical Analysis of the Conditionality of Generic Fear in the Prohibition of Casting (Throwing) in the Verse of Al-Tahluka Verse (Arabic: آیة التَّهْلُکَة, Destruction) - Muhammad Hassan Qasemi; Muhammad Imami; Mozhgan Ziaei (آموزه‌های قرآنی, 2023)
The verse “Spend your wealth in the cause of Allah and do not let your own hands throw you into destruction and…” is one of the verses of the Holy Quran that jurists have cited it in various discussions (Al-Baqarah, 2:195). There are many debates in determining the extent of the prohibition and how to interpret this verse, although the use of the prohibition of casting (throwing) from this verse is not debatable. This paper which has been done by descriptive analytical method, seeks to answer the question: Is the criterion of the prohibition of casting into Tahluka (Arabic: التَّهْلُکَة, destruction), probability, presumption, fear with individual criterion or generic fear? This research criticizes the presented criteria after stating the meaning of the verse and presenting the viewpoints and firstly, the presented criteria accepts the generality of casting into Tahluka (Arabic: التَّهْلُکَة, destruction), considering the criticisms of other views and considering that the case cannot limit (restrict) the general and expanded meaning of the verse and secondly, due to the fact that rulings are enacted on titles and subjects in Islamic Sharia (Arabic: شریعة, Romanized: sharīʿa) and it is also accepted the theory of generic fear that is the customary ruling for the destruction of the person due to the improbability of jurists’ obligation to personal fear essential concomitants and due to the recension (the effective cause) of the fatwā (Arabic: فتوی; plural fatāwā فتاوی) of jurists in verses such as the mentioned verse. Therefore, casting into Tahluka (Arabic: التَّهْلُکَة, destruction) is forbidden, if it is from the perspective of custom for the human race.